Peran Agroteknologi dalam Mendorong Pertanian Inovatif Berkelanjutan di Kabupaten Labuhanbatu: Irhamna Mandili Lubis*, Rahmi Sari Harahap, Rezki Tri Setya - Irhamna Mandili Lubis; Rahmi Sari Harahap; Rezki Tri Setya (Samudra Publisher, 2024)
This research aims to explore the perceptions, attitudes, challenges and strategies of farmers in Labuhanbatu Regency in adopting agrotechnology to encourage sustainable innovative agriculture. Using a qualitative approach, data was collected through in-depth interviews and focus group discussions with farmers representing various agricultural commodities. The research results show that the majority of farmers have a positive perception of agrotechnology, such as smart irrigation and superior plant varieties, which are considered capable of increasing agricultural productivity and efficiency. However, the adoption of this technology is faced with various challenges, including lack of knowledge and training, financial limitations, access to technology, and less than optimal institutional support. Farmers overcome this challenge with several strategies, such as utilizing social networks to share information and experiences, seeking education and training independently, as well as collaborating with the private sector and utilizing government assistance. These findings highlight the importance of sustainable, locally needs-based outreach and training programs, as well as policies that support more affordable access to technology and funding. This research also shows that synergy between various stakeholders, including government, the private sector, and extension institutions, is essential to encourage wider adoption of agrotechnology. Stronger support in the form of counseling, training and appropriate policies can accelerate the technology adoption process, thereby encouraging sustainable innovative agriculture in Labuhanbatu Regency.